2022
DOI: 10.35848/1882-0786/ac75a9
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric polymer thin-film memristors with asymmetric top electrodes

Abstract: A type of ferroelectric polymer thin-film memristors is demonstrated to show their potential in the emulation of synaptic plasticity. The memristive characteristics of the device arise from the design of asymmetric top electrodes capacitively coupled with a floating bottom electrode, which enables the local modulation of ferroelectric polarization in the ferroelectric terpolymer film. Basic synaptic functions, such as continuous increase/decrease in synaptic weight and paired-pulse facilitation, are successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…34 In recent years, several studies have adopted P(VDF−TrFE−CTFE) as the active layer in artificial synaptic devices. 35 These studies demonstrated the potential of this material for neuromorphic computing. However, there are still some challenges that need to be addressed to make the use of P(VDF−TrFE−CTFE) in artificial synaptic devices more feasible.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…34 In recent years, several studies have adopted P(VDF−TrFE−CTFE) as the active layer in artificial synaptic devices. 35 These studies demonstrated the potential of this material for neuromorphic computing. However, there are still some challenges that need to be addressed to make the use of P(VDF−TrFE−CTFE) in artificial synaptic devices more feasible.…”
Section: Introductionmentioning
confidence: 85%
“…Ferroelectric materials have spontaneous polarization that can be reversed by an external electric field. , This property makes them suitable for use in synaptic devices as it allows them to store and manipulate the synaptic weight in a similar manner to biological synapses. Therefore, ferroelectric materials have been widely studied for their potential applications in the development of artificial synaptic devices. One of the most promising ferroelectric materials is the organic ferroelectric material poly­(vinylidenefluoride–trifluoroethylene–chlorotrifluoroethylene) [P­(VDF–TrFE–CTFE)], which has been extensively investigated for its lower cost, lower processing temperature, and higher flexibility . In recent years, several studies have adopted P­(VDF–TrFE–CTFE) as the active layer in artificial synaptic devices . These studies demonstrated the potential of this material for neuromorphic computing.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been dedicated to the development of novel RS devices utilizing organic materials, such as organic monolayers [23], donor-acceptor-type copolymers [24], ferroelectric polymers [25], polymernanoparticle composites [26], and natural biomaterials [21]. Natural biomaterials are particularly promising due to their biodegradable, biocompatible, solution-processable, cost-effective, and eco-friendly nature [27,28].…”
Section: Introductionmentioning
confidence: 99%